FORMATION OF REFLEXIOUS ACTIVITIES OF ADOLESCENTS ON LITERATURE PRESENTATIONS - Спірідонова, Л. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2019)
The article is devoted to one of the stages of educational activity in literature lessons - the formation of reflection. The main attention is focused on revealing the essence of the concept of "reflection" and its effectiveness. The forms and methods of reflection at different stages of employment are singled out. Reflection is aimed at understanding the path taken, in gathering information. Such activity stimulates the moral development of students, and this affects their selectivity regarding the content process of ethical knowledge, emotional and personal attitude to the forms and methods of its organization. Activating the ability to reflect allows teenagers more adequately and actively to know reality, to reveal in its phenomena general and special, to develop new knowledge. Conducting reflection in classes is a kind of monitoring where the teacher can and must see whether each student (student, student) has made certain knowledge, results, expectations, and the ability of participants in the learning process to evaluate themselves and the work of others. Reflection helps the teacher to see the learning process and find out at once what was clear, and what’s left to refine. Reflection in the classroom is a joint activity of the students and the teacher, which allows to improve the educational process, focusing on the personality. At different stages, it has different functions: communicative, cognitive, motivational, corrective, and so on. Most psychologists and educators point out that written reflection is more important for the development of personality. One can distinguish several of the most well-known forms of written reflection: essay, free letter, mini-essay, on-board magazine.The realization of reflective activity in literature classes helps to more confident communication with peers and adults, reduce the level of unethical behavior of students, awareness of the acquired knowledge and skills, free expression of their feelings, development of the ability to reflect in real life, aware of their actions and to predict further steps, to compare their perception with thoughts, views, feelings of others, etc